Evaluation of the interactions of typical wood extracts on the bonding performance of soybean-based adhesives. (15th January 2023) - Liu, Zeshun; Mi, Yan; Kan, Yufei; Bai, Yumei; Li, Jianzhang; Gao, Zhenhua
Abstract: The substitution of environmentally friendly, renewable soybean-based adhesives (SBAs) for formaldehyde-based synthetic resins to produce formaldehyde-free wood composites is of great significance for resource recycling and environmental protection. However, SBA-bonded wood composites often exhibit great variations in bonding properties, due to the diverse interactions of the extractive components in wood. In this study, the extracts of four typical commercial fast-growing timbers were isolated, and their effects on the structures and properties of the SBAs were systematically investigated using FTIR, NMR, TGA, contact angle, buffer capacity, sol–gel test, and plywood evaluation. The analytical data indicated that some of the wood extracts could cause important effects on the bonding properties of the SBAs by impacting the PAE cross-linking capacity and unfolding degree of the globular soybean proteins. Fast-growing hardwood extracts from poplar and eucalyptus timbers containing active groups resulted in increased cross-linking density and improved water resistance of the SBAs. Meanwhile, fast-growing softwood extracts from Chinese fir and Scotch pine containing inert hydrophobic components had slight impacts on PAE cross-linking, but resulted in the agglomeration of unfolded soybean proteins. This formed a weak boundary layer on the wood surface, causing a significant decrease in the water resistance of the SBAs by >35%. These findings presented available analytic approaches of wood extract–SBA interactions and useful guidance for the proper applications of SBAs in the commercial production of wood composites. Highlights: The adhesion of soybean adhesive impacted by wood extracts was investigated. The interactions of the wood extracts with the crosslinker PAE were characterized. The interactions of wood extracts with soybean proteins were evaluated. The structure–property changes of the soybean adhesives caused by the wood extracts were revealed.